PENGARUH PENDIDIKAN TERHADAP KETIMPANGAN PENDAPATAN TENAGA KERJA DI INDONESIA - Ribut Nurul Tri Wahyuni; Anugerah Karta Monika (Research Centre for Population, Indonesian Institute of Sciences, 2016)
Education is an important factor in human resource investment. Education is also expected to increase income as well as decrease income inequality among workers. This paper analyzes returns to education in Indonesia. By processing the National Labor Force Survey data from six regions in Indonesia in 2013, we suggest a robust stylised fact: returns to education are higher for the more skilled individuals (workers who have high schooling). In other words, education can reduce income inequality. Income inequality occures because of over-education, ability–schooling interactions and school quality or different fields of study. Based on gender, returns to education for men is lower than for women. Education can reduce gender based income gap. Therefore, government can increase investment in education sector to reduce income inequality, including gender based income gap.